Tissue Bioengineering with Fibrin Scaffolds and Deproteinized Bone Matrix Associated or Not with the Transoperative Laser Photobiomodulation Protocol - Pomini, Karina Torres; Buchaim, Daniela Vieira; Bighetti, Ana Carolina Cestari; Hamzé, Abdul Latif; Reis, Carlos Henrique Bertoni; Duarte, Marco Antonio Húngaro; Alcalde, Murilo Priori; Barraviera, Benedito [UNESP]; Júnior, Rui Seabra Ferreira [UNESP]; de Souza, Alexandre Teixeira; da Silva Santos, Paulo Sérgio; Pilon, João Paulo Galletti [UNESP]; et al. (MDPI, 2023)
Extending the range of use of the heterologous fibrin biopolymer, this pre-clinical study showed a new proportionality of its components directed to the formation of scaffold with a lower density of the resulting mesh to facilitate the infiltration of bone cells, and combined with therapy by laser photobiomodulation, in order to accelerate the repair process and decrease the morphofunctional recovery time. Thus, a transoperative protocol of laser photobiomodulation (L) was evaluated in critical bone defects filled with deproteinized bovine bone particles (P) associated with heterologous fibrin biopolymer (HF). The groups were: BCL (blood clot + laser); HF; HFL; PHF (P+HF); PHFL (P+HF+L). Microtomographically, bone volume (BV) at 14 days, was higher in the PHF and PHFL groups (10.45 ± 3.31 mm3 and 9.94 ± 1.51 mm3), significantly increasing in the BCL, HFL and PHFL groups. Histologically, in all experimental groups, the defects were not reestablished either in the external cortical bone or in the epidural, occurring only in partial bone repair. At 42 days, the bone area (BA) increased in all groups, being significantly higher in the laser-treated groups. The quantification of bone collagen fibers showed that the percentage of collagen fibers in the bone tissue was similar between the groups for each experimental period, but significantly higher at 42 days (35.71 ± 6.89%) compared to 14 days (18.94 ± 6.86%). It can be concluded that the results of the present study denote potential effects of laser radiation capable of inducing functional bone regeneration, through the synergistic combination of biomaterials and the new ratio of heterologous fibrin biopolymer components (1:1:1) was able to make the resulting fibrin mesh less dense and susceptible to cellular permeability. Thus, the best fibrinogen concentration should be evaluated to find the ideal heterologous fibrin scaffold.
Keywords: biocompatible materials; biopolymers; bone regeneration; bone substitutes; fibrin sealant; low-level laser therapy; photobiomodulation; xenografts